The peculiar needs of deaf people: a study of selected members of the Lincolnshire deaf social group - Jones, K. (1989)
In spite of the fact that services for deaf people have been provided since Victorian times, there is no "philosophy of deafness" and services are based upon the subjective observation of deaf people by "hearing" people. This study seeks to formulate such a philosophy, for those unable to hear spoken communication from birth or early childhood, based upon acceptance of the social limitations of being unable to hear in a society where the ready use of that sense is taken for granted.